A Linguistic Analysis of Chinua Achebe’s Things Fall Apart: Rhetoric and Stylistic Study - Betu, Donat Nkuna (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
This article analyses linguistically Achebe’s style and rhetoric in Things Fall Apart. In particular, his use of ‘’African English’’, drawing on proverbs, tales, and idioms of the Igbo culture, some borrowings from his native tongue, and some writing techniques used. This novel is written by Chinua Achebe, a Nigerian writer, and he interposes Western linguistic forms and literary traditions to record and preserve African Oral traditions as well as to subvert the colonialist language and culture.